Fruit ripeness grading system. - Mohamed Sharif, Abdul Rashid; Abdullah, Mohd. Zaid; Marhaban, Mohammad Hamiruce; Suhaidi Shafie, Suhaidi; Amiruddin, Mohd. Din; Alfatni, Meftah Salem M. (2010)

(untitled)
A fruit ripeness grading system which used computer vision application in agricultural quality inspection to ensure ripeness category of fruit characterized in that, the fruit ripeness grading system includes: a) a housing having an enclosure for scanning process; b)an illumination means with optical lens illumination filter provided at the enclosure of the housing; c) a camera provided at top portion of the enclosure of the housing; d) a feeding device for conveying fruit samples to the housing; e) conveyer speed inverter; f) a processing unit process and analyze the fruit sample image; g) a data acquisition interface provided in between the camera and the processing unit; wherein the feeding device further provided with separator controlled by USB controller and supported by compressor for controlling and separating the fruit samples; wherein the processing unit further provided with a disk top computational unit serves to transfer data to a computer.